Catalyst Screening for Oxidative Coupling of Methane Integrated in Membrane Reactors - Garcia-Fayos, Julio; Lobera, Maria P.; Balaguer, Maria; Serra, Jose M. (Frontiers in Materials, 2018)
Increased availability of methane from shale gas and stranded gas deposits in the recent years may facilitate the production of ethylene by means of potentially more competitive routes than the state-of-the-art steam cracking processes. One appealing route is the oxidative coupling of methane (OCM), which is considered in this work for the production of ethylene by means of the use of catalytic membrane reactors (CMR) based on Ba0.5Sr0.5Co0.8Fe0.2O3 (BSCF) ceramic material. In a first approach, a screening of 16 formulations as catalysts for the ethylene-ethane production was conducted on CMR consisted of disk-shaped planar BSCF membranes. At 900 ºC, the maximum C2 selectivity was 70%, reached with Ba0.5Sr0.5FeO3 and La0.5Ce0.1Sr0.4Co0.8Fe0.2O3 catalysts. On the other hand, low CH4 conversions (XCH4) resulted in C2 yields below 3%. Operation at 1000 ºC significantly shifted XCH4 for all the activated membranes due to the decrease in CH4/O2 ratios, thus obtaining C2 yields close to 9% and productivities of ca. 1.2 ml·min-1·cm-2 with Ce0.9Gd0.1O2 and Ba0.5Sr0.5Co0.8Fe0.2O3 impregnated with Mn-Na2WO4 catalysts. The performance of OCM reaction was also studied in a tubular catalytic membrane reactor. Tubular configuration improved C2 yield by minimizing CH4/O2 ratios up to 1.7, obtaining a maximum of 15.6% at 900 ºC with a BSCF capillary membrane activated with a packed bed of 2 wt% Mn / 5 wt% Na2WO4 on SiO2 catalyst.